Detained introns are a novel, widespread class of post-transcriptionally spliced introns - Boutz, Paul L.; Bhutkar, Arjun; Sharp, Phillip A. (Genes & development, 2015)
Deep sequencing of embryonic stem cell RNA revealed many specific internal introns that are significantly more abundant than the other introns within polyadenylated transcripts; we classified these as “detained” introns (DIs). We identified thousands of DIs, many of which are evolutionarily conserved, in human and mouse cell lines as well as the adult mouse liver. DIs can have half-lives of over an hour yet remain in the nucleus and are not subject to nonsense-mediated decay (NMD). Drug inhibition of Clk, a stress-responsive kinase, triggered rapid splicing changes for a specific subset of DIs; half showed increased splicing, and half showed increased intron detention, altering transcript pools of >300 genes. Srsf4, which undergoes a dramatic phosphorylation shift in response to Clk kinase inhibition, regulates the splicing of some DIs, particularly in genes encoding RNA processing and splicing factors. The splicing of some DIs—including those in Mdm4, a negative regulator of p53—was also altered following DNA damage. After 4 h of Clk inhibition, the expression of >400 genes changed significantly, and almost one-third of these are p53 transcriptional targets. These data suggest a widespread mechanism by which the rate of splicing of DIs contributes to the level of gene expression.